(untitled) (The Pakistan Development Review, 1989)
This paper presents a quantitative analysis of adjustment programmes. This is done by charting changes in various performance indicators fonowing the receipt of the first adjustment loan, and by further contrasting the results with those for the comparator group of countries that did not receive adjustment loans. h is found that the average decline in the GOP growth rate in the loan-recipient countries was less than in the comparator groups. Similar results were obtained in regard to per capita GOP. At the same time, in both cases, a majority of loan-recipient countries experienced an improvement in their relative position vis-d-vis the nonrecipient s. It is further apparent that the loan-recipient countries made an adjustment effort in the period following the fIrst loan. To begin with, economic expansion was concentrated in the traded goods sectors, industry and agriculture, both of which experienced an improvement in the loan-recipient countries relative to the comparator groups. Also, the growth of consumption declined substantially in absolute terms as well as relative to the non-recipient countries. In turn, an acceleration is observed in the growth of investment that holds the promise for future economic growth.